Case report: Uncontrollable coronary artery perforation caused by severe stenosis proximal to loopy vessels - Zeng, Yuan; Lu, Lin; Wei, Gang; Zheng, Wenwu; Chen, Gong (Frontiers in Cardiovascular Medicine, 2025)
Coronary artery perforation(CAP) is a rare but potentially life-threatening event. Typically, such complications can be effectively managed with appropriately placed covered stents or embolization. However, in special cases, these methods may prove less effective. Here, we present a case of CAP requiring emergency surgical suturing: a perforation caused by radial cutting of the guidewire in a tortuous coronary lesion, accompanied by rapid opening of distal side branches in a narrowed vessel.